Características higiênicas e sanitárias em propriedades produtoras de leite de assentamento da Região Noroestedo Estado de São Paulo - De Oliveira, Talita C. Bragança [UNESP]; Curci, Vera C.L. Magalhães; Alves, Ana Julia Silva; Morelli, Fernando Christiano Gabriel [UNESP]; Buso, Daniel Sartore [UNESP]; Queiroz, Luzia Helena [UNESP] (My University, 2015)
In order to check the hygienic and sanitary conditions of milk-producing farms from a settlement located at the northwestern region of São Paulo State, 62 of the resident families (246 people) were interviewed by using a questionnaire which addressed since issues concerning to general infrastructure until animal health management. The results showed that: in all the farms water comes from wells and the sewage is disposed in septic tanks; the burning of domestic waste is a common practice in 90.3% of the farms; the average dairy herd cattle is 30.6 and the purchase of new animals is done from other farms within the same settlement; in all properties veterinary care is provided by ITESP's (Land Institute of São Paulo State) technicians and mastitis was the main disease of the herds occurring in 59,7% of the farms. Milk is collected in buckets or drums that are daily cleaned and stored in communal tanks distributed by the settlement. Alizarol is the only test performed every day. 100% of the farmers vaccinate their animals against foot and mouse disease and brucellosis, according to Official vaccination program. 62.9% of the interviewed owners do not eliminate correctly the carcasses. This study shows that properties needs infrastructure improvements, training of settlers to implementing measures of general and health management as well as special attention to the quality of the final generated products.
Hygienic and sanitary characteristics in milk-producing farms of settlement in northwestern São Paulo State
Keywords: Andradina; Health management; Milk production; Rural settlements; São Paulo